Can Educators Thrive? : Pilot Study of a Multi-Component Educator Well-being Professional Development Intervention - Fox, Harriet; Hester, Weston Tyler; Wasil, Akash (Journal of Interdisciplinary Studies in Education, 2023)
Given growing interest in strategies to support teacher retention and well-being, research has focused on evaluating interventions that both reduce threats to well-being and also develop competencies to increase well-being. The present study focused on a pilot evaluation of the Educators Thriving program, which targeted educator burnout, resilience, and well-being. We performed an observational study in which participants who received a multi-component professional development intervention were compared to teachers who did not participate in the program. Relative to educators in a comparison group, we found that educators in the intervention group reported greater improvements in burnout, resilience, depressive symptoms, and anxiety symptoms. These results are promising, suggesting that multi-component professional development interventions may be an effective means by which to support the well-being and personal development of teachers.